Sistem Informasi Pengelolaan Persediaan Obat Menggunakan Metode Economic Order Quantity (EOQ) Pada Apotek Rian Farma (Studi Kasus: Apotek Rian Farma) - Erlan Darmawan (Sistem Informasi Fakultas Ilmu Komputer Universitas Kuningan, 2018)
Rian Farma Pharmacies still uses manual management system of drugs inventory so that it can be lost or damaged, and at the time, the bookkeeping and data checking medication take too long so that the pharmacy is difficult to manage the supply of drugs quickly and it is difficult to plan a number of booking which will be ordered. Based on the condition, the writer creates a design system for the management of drug stocks at Rian Farma pharmacy which aims to facilitate the pharmacy to manage inventory stock of drugs such as goods in and goods out and for planning reserve in the amount of stock that will be the ordered. In inventory management information system, the writer uses Economic Order Quantity (EOQ). It is a method for determining the amount of the minimum limit stock and the amount of stock to be ordered. The system development uses Waterfall method. Waterfall has several stages in building a system such as analyzing, designing, coding, testing and maintaining. The stages are mutually continuous and repeated to form a waterfall. By using this system, Rian Farma pharmacy can find out how the optimal number of orders booked back to the supplier so that the stock of drugs in the warehouse can be optimal. The reporting process is fast and accurate, and easy to search the data because it is integrated with the database so that the controlling stock of the drug is easier and faster